2018
DOI: 10.1111/cup.13282
|View full text |Cite
|
Sign up to set email alerts
|

Poroid hidradenoma in the hand: A case report and systematic review

Abstract: Poroid hidradenoma (PH) is a rare benign neoplasm of the skin appendages. There are currently no guidelines for its management, and little information available regarding the natural history, treatment options, or outcomes. Systematic literature review identified 19 cases of isolated PH. Mean age at presentation was 54 years. Male to female ratio was 3:1, and the majority of cases were in the head and neck region. One-third of lesions were painful or tender. Sizes varied from 0.11 × 0.9 × 0.2 cm (digit) to 6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 10 publications
(7 reference statements)
0
17
0
Order By: Relevance
“…PH is a form of hidradenoma with eccrine differentiation according to the WHO classifications of skin tumors 1 . The age of onset ranges widely, with a peak incidence in the seventh decade of life 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PH is a form of hidradenoma with eccrine differentiation according to the WHO classifications of skin tumors 1 . The age of onset ranges widely, with a peak incidence in the seventh decade of life 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant site of involvement is the head and neck region, followed by the axilla, trunk, and extremities 4 . Miller et al 1 reported the systematic reviews of PH, which occur more commonly in male, in the head and neck region or limbs. Considering that these neoplasms can be generally asymptomatic or accompanied by mild tenderness, the incidence of PHs might be underestimated in the literature 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting with this condition range from ages 13 to 91 with the disease being more common in the sixth and seventh decades of life [ 6 ]. Some authors say that the incidence in males and females is about equal while others say that the male to female ratio is 3:1 [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Miller et al. recommended 6 months to 1 year follow-up since they did find one case of possible recurrence, and they recommended marginal excisions since there are no reports of malignant transformation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%